Versatile power and energy conversion of magnetoelectric composite materials with high efficiency via electromechanical resonance. (April 2020) - PourhosseiniAsl, MohammadJavad; Gao, Xiangyu; Kamalisiahroudi, Sara; Yu, Zhonghui; Chu, Zhaoqiang; Yang, Jikun; Lee, Ho-Yong; Dong, Shuxiang
Abstract: A better understanding of magnetoelectric (ME) energy materials with superior properties stimulates exploration of next generation of versatile energy devices with a high efficiency. Although a number of investigations have focused on developing multiferroic composite materials because of their potential in cutting-edge multifunctional devices, advances in basic research have not yet been translated into benefits for practical applications. In the present investigation, we introduce a two-phase magnetoelectric composite made of nanocrystalline FeBSi metallic ribbons (Metglas) and Mn 3+, 2+ acceptor doped Pb(Mg1/3 Nb2/3 )O3 –Pb(Zr, Ti)O3 (PMN-PZT) single crystal, and great enhancements in ME coupling coefficient (αME 12500 V/Oe cm) with a tunable resonance frequency, current-to-voltage ( I–V ) conversion ratio ( 15090 V/I), as well as power conversion efficiency ( η 95% ) are found at the fundamental electromechanical resonance, which represent the highest values ever reported. This study also provides a fundamental understanding of the role of a figure of merit ( FOM), k ij, eff × Q m, eff, on ME coupling performances in ferromagnetic and ferroelectric two-phase ME composite. The enhanced performances are attributed to the laser heat treatment induced Nano crystallization in Metglas, lower magnetic and dielectric loss (tan δ ), and also higher mechanical quality factor ( Q m, eff ) in ME composite. This research opens up the possibilities of developing ME composite materials for next-generation versatile energy and power conversion devices. Graphical abstract: Image 1 Highlights: Both soft PMN-PT and hard PMN-PZT single crystals were grown by the solid-state single crystal growth method. Both Qm, eff and k ij, eff in two-phase composite play key roles toward a colossal ME voltage coefficient of 12500 V/cm Oe. This study provides a fundamental understanding of the role of a figure of merit on Magnetoelectric coupling performances. An ultra-high power efficiency (95%), a great I–V conversion of 15090 V/A and voltage gain in ME gyrators are achieved.